Faktor-Faktor Yang Mempengaruhi Keputusan Mahasiswa Memilih Program Studi Ilmu Komunikasi Untuk Menentukan Strategi Komunikasi Pemasaran Fikom Budi Luhur - Bintarto Wicaksono; Rini Lestari; Mulyati Mulyati (Fakultas Komunikasi & Desain Kreatif - Universitas Budi Luhur, 2019)
This research is based on the question of what factors influence students in choosing the Communication Studies program at Budi Luhur University, Jakarta, which will then be used as forms of strategy in promotion. This research is a quantitative study using survey methods. Information is extracted and presented using the Factor Analysis method. The stages in this research begin with the study of literature, determining variables and indicators. Field data collected through the distribution of questionnaires are presented in accordance with available facts, organized and systematic. The results of this study indicate that the most dominant factor of students deciding to choose the Communication Studies study program is the reference group factor, namely suggestions from teachers, friends, and parents. Furthermore, the results of the research were revealed in the promotion strategies by the Promotion Team of new students at Budi Luhur University Jakarta.